Dysregulated insulin secretion is associated with pancreatic β‐cell hyperplasia and direct acinar‐β‐cell trans‐differentiation in partially eNOS‐deficient mice. Issue 16 (19th August 2022) - Novelli, Michela; Masini, Matilde; Vecoli, Cecilia; Moscato, Stefania; Funel, Niccola; Pippa, Anna; Mattii, Letizia; Ippolito, Chiara; Campani, Daniela; Neglia, Danilo; Masiello, Pellegrino
Abstract: eNOS‐deficient mice were previously shown to develop hypertension and metabolic alterations associated with insulin resistance either in standard dietary conditions (eNOS−/− homozygotes) or upon high‐fat diet (HFD) (eNOS+/− heterozygotes). In the latter heterozygote model, the present study investigated the pancreatic morphological changes underlying the abnormal glycometabolic phenotype. C57BL6 wild type (WT) and eNOS+/− mice were fed with either chow or HFD for 16 weeks. After being longitudinally monitored for their metabolic state after 8 and 16 weeks of diet, mice were euthanized and fragments of pancreas were processed for histological, immuno‐histochemical and ultrastructural analyses. HFD‐fed WT and eNOS+/− mice developed progressive glucose intolerance and insulin resistance. Differently from WT animals, eNOS+/− mice showed a blunted insulin response to a glucose load, regardless of the diet regimen. Such dysregulation of insulin secretion was associated with pancreatic β‐cell hyperplasia, as shown by larger islet fractional area and β‐cell mass, and higher number of extra‐islet β‐cell clusters than in chow‐fed WT animals. In addition, only in the pancreas of HFD‐fed eNOS+/− mice, there was ultrastructural evidence of a number of hybrid acinar‐β‐cells, simultaneously containing zymogen and insulin granules, suggesting the occurrence of a direct exocrine‐endocrine transdifferentiation process, plausibly triggered by metabolic stress associated to deficient endothelial NO production. As suggested by confocal immunofluorescence analysis of pancreatic histological sections, inhibition of Notch‐1 signaling, likely due to a reduced NO availability, is proposed as a novel mechanism that could favor both β‐cell hyperplasia and acinar‐β‐cell transdifferentiation in eNOS‐deficient mice with impaired insulin response to a glucose load. Abstract : In heterozygous eNOS+/− mice, fed with either standard or high fat diet (HFD), blood insulin increase in response to a glucose load is impaired, combined with overt glucose intolerance and insulin resistance upon HFD. This pattern is associated with pancreatic β‐cell hyperplasia and, in HFD‐fed mice only, with ultrastructural evidence of hybrid acinar‐β cells, a likely result of a direct exocrine‐endocrine transdifferentiation process. Inhibition of Notch‐1 signalling documented in pancreatic cells is suggested as a putative molecular mechanism linking reduced NO availability with dysregulated pancreatic endocrine function and morphological changes.